Paradise lost? Pesticide pollution in a European region with considerable amount of traditional agriculture. (1st January 2021) - Schreiner, Verena C.; Link, Moritz; Kunz, Stefan; Szöcs, Eduard; Scharmüller, Andreas; Vogler, Bernadette; Beck, Birgit; Battes, Karina P.; Cimpean, Mirela; Singer, Heinz P.; Hollender, Juliane; Schäfer, Ralf B.
Highlights: Pesticide concentrations and toxicity similar along agricultural gradient. Sum concentrations in Romanian streams ranged from 0.02 to 37 μg L −1 . Agricultural intensity not related to pesticide concentration and toxicity. Toxicity towards invertebrates and algae driven by few pesticides. Catchment size and ratio agricultural land use were related to invertebrate toxicity. Abstract: Pesticide contamination of agricultural streams has widely been analysed in regions of high intensity agriculture such as in Western Europe or North America. The situation of streams subject to low intensity agriculture relying on human and animal labour, as in parts of Romania, remains unknown. To close this gap, we determined concentrations of 244 pesticides and metabolites at 19 low-order streams, covering sites from low to high intensity agriculture in a region of Romania. Pesticides were sampled with two passive sampling methods (styrene-divinylbenzene (SDB) disks and polydimethylsiloxane (PDMS) sheets) during three rainfall events and at base flow. Using the toxic unit approach, we assessed the toxicity towards algae and invertebrates. Up to 50 pesticides were detected simultaneously, resulting in sum concentrations between 0.02 and 37 µg L -1 . Both, the sum concentration as well as the toxicities were in a similar range as in high intensity agricultural streams of Western Europe. Different proxies of agricultural intensity did not relate to in-stream pesticide toxicity, contradicting the assumption of previous studies. The toxicity towards invertebrates was positively related to large scale variables such as the catchment size and the agricultural land use in the upstream catchment and small scale variables including riparian plant height, whereas the toxicity to algae showed no relationship to any of the variables. Our results suggest that streams in low intensity agriculture, despite a minor reported use of agrochemicals, exhibit similar levels of pesticide pollution as in regions of high intensity agriculture. Graphical abstract: Image, graphical abstract